Heart berries ebook A memoir. - Mailhot, Terese Marie (2018)
A powerful, poetic memoir of an Indigenous woman's coming of age on the Seabird Island Band in the Pacific Northwest—this New York Times bestseller and Emma Watson Book Club pick is “an illuminating account of grief, abuse and the complex nature of the Native experience . . . at once raw and achingly beautiful (NPR). Having survived a profoundly dysfunctional upbringing only to find herself hospitalized and facing a dual diagnosis of post traumatic stress disorder and bipolar II disorder, Terese Marie Mailhot is given a notebook and begins to write her way out of trauma. The triumphant result is Heart Berries , a memorial for Mailhot's mother, a social worker and activist who had a thing for prisoners; a story of reconciliation with her father―an abusive drunk and a brilliant artist―who was murdered under mysterious circumstances; and an elegy on how difficult it is to love someone while dragging the long shadows of shame. Mailhot trusts the reader to understand that memory isn't exact, but melded to imagination, pain, and what we can bring ourselves to accept. Her unique and at times unsettling voice graphically illustrates her mental state. As she writes, she discovers her own true voice, seizes control of her story, and, in so doing, reestablishes her connection to her family, to her people, and to her place in the world.